1990
DOI: 10.1210/endo-127-4-1978
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Thyrotropin-Releasing Hormone (TRH) Prohormone in the Rat Olfactory Bulb Generates Novel TRH-Related Peptides*

Abstract: Based on the deduced amino acid sequence of rat TRH prohormone (pro-TRH), proteolytic processing of this polyprotein precursor is expected to produce, beside TRH, several other novel peptides. These peptides should correspond to connecting segments flanking the repeated TRH progenitor sequence and to various C- and/or N-terminally extended forms of TRH. The profile of the endogenous products of the TRH system was studied in rat brain using multiple RIAs coupled to molecular sieve filtration and HPLC separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…has been reported to pro mote the expression of TSH (i-subunit mRNA in rat thyrotropes [ l], to enhance rat pituitary synthesis and release of prolactin [ l], and to enhance the in vitro release of thy roid-stimulating hormone from rat anterior pituitaries in response to TRH (p-Glu-His-Pro-NH;;), but lacks intrin sic thyroid-stimulating hormone releasing activity [2,3], Infusion of PS4 into the raphe nucleus of the medulla also increases TRH-induced gastric acid secretion of rats [4], A specific receptor for PS4 has been identified in the plas ma membrane of rat anterior pituitaries [5, 6], We have previously reported that electroconvulsive seizures (ECS) produce a sustained increase in TRH and TRH-Gly in limbic regions of the rat brain which corre lates with an antidepressant effect as measured in the Porsolt forced swim test [7). mRNA levels for enzymes responsible for proteolytically cleaving prepro-TRH, and other neuropeptides, are also increased by ECS [8].…”
Section: Introductionmentioning
confidence: 99%
“…has been reported to pro mote the expression of TSH (i-subunit mRNA in rat thyrotropes [ l], to enhance rat pituitary synthesis and release of prolactin [ l], and to enhance the in vitro release of thy roid-stimulating hormone from rat anterior pituitaries in response to TRH (p-Glu-His-Pro-NH;;), but lacks intrin sic thyroid-stimulating hormone releasing activity [2,3], Infusion of PS4 into the raphe nucleus of the medulla also increases TRH-induced gastric acid secretion of rats [4], A specific receptor for PS4 has been identified in the plas ma membrane of rat anterior pituitaries [5, 6], We have previously reported that electroconvulsive seizures (ECS) produce a sustained increase in TRH and TRH-Gly in limbic regions of the rat brain which corre lates with an antidepressant effect as measured in the Porsolt forced swim test [7). mRNA levels for enzymes responsible for proteolytically cleaving prepro-TRH, and other neuropeptides, are also increased by ECS [8].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have been focused on the fourth connecting peptide, termed Ps4, a decapeptide (Ser-Phe-Pro-Trp-Met-Glu-SerAsp-Val-Thr) linking the third and fourth copies of the TRH progenitor. It was first demonstrated that posttranslational processing of pro-TRH generates authentic Ps4 in the olfactory lobe, hypothalamus, and spinal cord (2) and in the pancreas (3). Immunocytochemical studies have subsequently revealed the existence of a dense accumulation of Ps4-containing nerve terminals in the external zone of the median eminence (4).…”
mentioning
confidence: 99%
“…Proteolytic processing of the rat precursor is expected to produce five copies of TRH along with several connecting peptides and various C-and/or N-terminally extended forms of TRH. A variety of data have provided evidence for the coexistence of partial and complete processing of pro-TRH in various regions of the rat brain (Cockle and Smyth 1987;Wu et al 1987;Bulant et al 1988). Like other neural peptides, TRH occurs outside the CNS in neuroendocrine cells.…”
mentioning
confidence: 99%